Effect of Bank of Terms and Rotator Circle Strategies in Achievement of social studies subject and Reflective Thinking for the Second Middle Grade Students (Journal of the College of Basic Education, 2024)
This research aims at identifying the effect of bank of terms and rotator circle strategies in achievement of social studies and Reflective thinking for second middle grade students. The study sample consists of (96) students, divided into two experimental groups, the first one studied the Geography based on bank of terms method which includes (33) students while the second experimental group which consists of (33) students, studied the same subject according to the rotator circle, and the control group includes (32) students studied via the traditional method. The researcher compare between variables of the three groups regarding (the chronological age, intelligence test, previous knowledge and Reflective thinking), the first tool has established an achievement test includes (50) items, while the researcher prepared a second tool which was represented in a Reflective thinking test consists of (30) items, the researcher verified its reliability, validity and psychometric properties. The study`s findings that the two experimental groups are outperformed the control group.